Teaching for citizenship in urban schools - Castro, Antonio J.; Cuenca, Alexander, 1979-; Williamson, Jason (Teaching and learning social studies., 2020)
"As the civic engagement gap widens across lines of race, class, and ethnicity, educators in today's urban schools must reconsider what it means to teach for citizenship; however, few resources exist that speak to their unique contexts. Teaching for Citizenship in Urban Schools offers lessons and strategies that combines the power of inquiry-driven teaching with a funds of knowledge approach to capitalize on the lived civic experiences of urban youth and children. Teaching for Citizenship in Urban Schools presents six strategies for making civic and social studies education relevant and engaging: using photovoice for social change, conducting culturally responsive investigations of community, defining American Black founders, enacting hip-hop pedagogy, employing equity literacy to explore immigrant enclaves, and drawing on young adult fiction to teach about police violence. Written by some of the leading scholars in the field, each chapter includes an overview of the strategy and lessons for both elementary and secondary students. As a whole, these lessons draw on neighborhood resources, facilitate cultural exchanges among students and teachers, create community networks, and bridge schools and communities in a shared mission of building a just and incluscive democracy. This book is for anyone who values student-centered, inquiry-driven, and culturally-sustaining pedagogies that foster a deeper understanding of citizenship within a diverse democracy"--